Association between residual cholesterol and vulnerable non-culprit lesions progressing to major adverse cardiovascular events - Fengfeng Wang; Qun Li (Frontiers in Endocrinology)
BackgroundResidual cholesterol (RC), a key indicator of lipid metabolism disorders, has been increasingly implicated in atherosclerotic progression. However, its association with vulnerable thin-cap fibroatheromas (TCFA) in non-culprit coronary lesions (NCCLs) and the subsequent risk of major adverse cardiovascular events (MACE) remains insufficiently explored.MethodsIn this prospective observational study conducted between June 2022 and September 2023, patients diagnosed with TCFA within NCCLs were followed for at least 12 months. Participants were grouped according to MACE occurrence. Spearman correlation and multivariate logistic regression were used to examine associations between RC levels, plaque vulnerability features, and MACE.ResultsRC showed significant correlations with key vulnerability markers—negatively with fibrous cap thickness (rs = -0.61, P < 0.001) and positively with lipid arc (rs = 0.75, P < 0.001). In univariate analysis, elevated RC was associated with a 1.88-fold increased risk of MACE. RC remained an independent risk factor in multivariate analysis (OR = 1.127, 95% CI: 1.101–1.593, P = 0.031). ROC analysis yielded moderate predictive value (AUC = 0.720).ConclusionElevated RC is associated with greater plaque vulnerability and increased MACE risk in patients with NCCL-TCFA. These findings suggest RC’s potential role in cardiovascular risk stratification, warranting further validation in larger studies.